ڈاکٹر فضل الرحمٰن کی اردو تحریریں اور تراجم: (ایک جائزہ) - نوین حیدر (FIKR-O NAZAR فکر ونظر, 2009)
Dr. Fazlur Rahman, a controversial intellectual, on one hand, is criticized severely for his close association with General Ayub Khan during 1960s and on the other hand he is highly praised for his deep and thorough scholarship and contribution to Islamic thought, which is accessable to the scholars through his English writings. However, most Scholars remain unaware of Fazlur Rahman’s work available in Urdu because of the language barrier as well as other factors. Fazlur Rahaman while being a leading scholar associated with Islamic Research Institute regularly contributed articles in the Institute’s Urdu Journal Fikr-o-Nazar.Moreover, under Fazlur Rahman’s own supervision some scholars had translated some of his highly academic and technically difficult works into Urdu; these are all preserved in the pages of Fikr-o-Nazar. Some Urdu translations, though of not very high quality, of his English works are also current. This paper is an attempt to introduce Fazlur Rahman’s original Urdu writings as well as his works translated in Urdu for the benefit of researchers and scholars.